INTEGRATING COGNITIVE SEMANTICS AND DIGITAL METHODS IN THE ANALYSIS OF MEANING CONSTRUCTION - Khudoyberganova Nozimakhon Bakhtiyor kizi (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
Cognitive semantics has become a central direction in modern linguistics because it conceptualizes meaning as a dynamic interpretive process grounded in encyclopedic knowledge, cognitive operations, and discourse context. Simultaneously, digital methods-corpus tools, computational procedures, and visualization-have expanded the empirical base of linguistic research and strengthened replicability. This article presents how cognitive semantics can be integrated with digital analysis for investigating meaning construction in discourse. The study systematizes cognitive-semantic mechanisms relevant for methodological innovation (frame/scenario activation, prototype-based categorization, conceptual metaphor and metonymy, blending, and cognitive mapping) and proposes a hybrid workflow that combines qualitative modeling with corpus-supported validation and network visualization. As results, the article provides a replicable procedure for tracing metaphorical framing and frame transformations in discourse and demonstrates how conceptual relations can be represented as networks. The discussion highlights the benefits of cognitive-digital integration for transparency and large-scale interpretive research and argues that the hybrid approach preserves explanatory depth while adding empirical control.